Additive manufacturing of high-performance 15-5PH stainless steel matrix composites. Issue 2 (3rd April 2022) - Chen, Wei; Xu, Lianyong; Zhang, Yankun; Han, Yongdian; Zhao, Lei; Jing, Hongyang
ABSTRACT: The consolidation of ceramic particles into the metallic matrix is promising to translate their exceptional properties from the micro-scale to the macro world. Herein, four different 15-5PH stainless steel (SS) matrix composites: 15-5PH/TiB2, 15-5PH/TiN, 15-5PH/TiC and 15-5PH/WC were fabricated by directed energy deposition (DED). The introduction of TiB2 particles substantially refines the martensite grain size, however, fails to achieve the performance improvement due to the elemental segregation of Cr and formation of considerable macro- and micro-cracks. The TiN composite realises a simultaneous enhancement of strength and ductility due to grain refinement, however, fails to enhance the corrosion resistance due to the Cr element segregation. The WC and TiC composites achieve the balance between the improved strength and ductility coupled with simultaneous enhancement of corrosion resistance. This work demonstrates the substantial potential in developing martensitic SS matrix composites with excellent strength-ductility synergy and corrosion resistance.